The Correlation of Clinicopathological Features With the Status of Surgical Margins in Renal Cell Cancer Patients Following Nephron-Sparing Surgery: A Systematic Review and Meta-Analysis - Zhang, Lijin; Wu, Bin; Zha, Zhenlei; Zhao, Hu; Yuan, Jun; Feng, Yejun (Frontiers in Oncology, 2019)
Objectives: The aim of this study was to evaluate the correlation of various clinicopathological variables with positive surgical margins (PSMs) in renal cell cancer (RCC) patients after nephron-sparing surgery (NSS). Methods: A systematic search of PubMed, EMBASE, Web of Science, and China National Knowledge Infrastructure (CNKI) was performed to identify studies that compared PSMs with negative surgical margins (NSMs) and were published up to December 2018. Outcomes of interest included perioperative and postoperative variables, and the data were pooled by odds ratios (ORs) / standard mean differences (SMD) with 95% confidence intervals (CIs) to evaluate the strength of such associations. STATA 12.0 software was used for all statistical analyses. Results: Based on the inclusion and exclusion criteria, thirteen studies including 47,499 patients with RCC were analyzed. The results showed that higher Furhman grade (pooled OR=1.25; 95% CI: 1.14–1.37; P<0.001), higher pathological stage (pooled OR=2.67; 95% CI: 2.05–3.50; P<0.001), non-clear cell RCC (non-ccRCC) histology (pooled OR=0.78; 95% CI:0.72–0.84; P<0.001) and non-white race (pooled OR=0.90; 95% CI:0.82–0.99; P=0.026) were significantly associated with high risk of PSMs. However, age (pooled SMD=0.09; 95% CI: -0.01–0.20; P=0.078), gender (female vs. male) (pooled OR=1.04; 95% CI: 0.96–1.12; P=0.377), tumor laterality (left vs. right) (pooled OR=1.09; 95% CI: 0.84–1.42; P=0.501), tumor focality (unifocal vs. multifocal) (pooled OR=0.67; 95% CI: 0.23–1.90; P=0.445), tumor size (pooled SMD=0.03; 95% CI: -0.10–0.15; P=0.685), and surgical approach (open vs. non-open) (pooled OR=0.94; 95% CI: 0.62–1.42; P=0.763) had no relationship with PSMs. Sensitivity analysis showed that all models were stable, and no publication bias was observed in our study. Conclusions: The present findings demonstrate that the presence of PSMs was associated with higher Furhman grade and higher pathological stage. Additionally, non-white patients with non-ccRCC histology had a high risk of PSMs after NSS. Further multicenter and long-term follow-up studies are required to verify these findings.